Factors that Influence the Seafaring Households Financial Management in Jatibogor Village, Suradadi District, Tegal Regency - Akhris Fuadatis Sholikha (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2021)
This objective of study is to determine the factors that influence the financial management of seafaring households in Jatibogor Village, Suradadi District, Tegal Regency. In this study, researchers examined several factors, namely family income, financial education in the family, financial knowledge, lifestyle, and spiritual intelligence. This type of research used associative hypothesis research. The study took a sample of seafaring households in Jatibogor Village, Suradadi District, Tegal Regency, where the respondent in this study is a wife. While the data in this study were processed using multiple linear regression analysis. The results showed that family income and financial knowledge had no influence on financial management of seafaring households in Jatibogor Village, Suradadi District, Tegal Regency, but financial education, lifestyle, and spiritual intelligence influenced the financial management of seafaring household in Jatibogor Village, Suradadi District, Tegal Regency.